Non-dietary methods in the treatment of celiac disease - Szaflarska-Popławska, Anna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
This is a selective review of the literature concerning the methods of celiac disease treatment, which can be an alternative to a gluten-free diet. The most advanced studies are devoted to the larazotide acetate (AT-1001, human zonulin inhibitor) and prolyl-endopeptidases degrading toxic gluten peptides (ALV003, AN-PEP). It is estimated that they will be registered within a few years. They will not become an alternative to the gluten-free diet but rather a supplement to it, which will enable patients to ease the nutritional restrictions.